Modernity and Spirit Worship in India An Anthropology of the Umwelt - Ishii, Miho (Routledge New Horizons in South Asian Studies, 2020)
This book investigates the entangled relations between people's daily worship practices and their umwelt in South India. Focusing on the practices of spirit (būta) worship in the coastal area of Karnataka, it examines the relationship between people and deities. Based on extensive fieldwork, this book links important anthropological theories on personhood, perspectives, transactions, and gift-exchanges together with the Gestaltkreis theory of Viktor von Weizsäcker. First, it examines the relations between būta worship and land tenure, matriliny, and hierarchy in the society. It then explores the reflexive relationship between modern law and current practices based on conventional law, before examining new developments in būta worship with the rise of mega-industries and environmental movements. Furthermore, this book sheds light on the struggles and endeavours of the people who create and recreate their relations with the realm of sacred wildness, as well as the formations and transformations of the umwelt in perpetual social-political transition. Modernity and Spirit Worship in India will be of interest to academics in the field of anthropology, religious studies and the dynamics of religion, and South Asian Culture and Society.